Acquisition finance and market timing - Vermaelen, Theo; Xu, Moqi (Journal of Corporate Finance, 2014)
Bidders have an incentive to pay with stock when their shares are overvalued, but target firms should be reluctant to accept such overvalued payment. In a sample of 2978 acquisitions, we find that stock payment is readily accepted only when the bidder can justify the financing decision in terms of such economic fundamentals as optimal capital structure. Yet even when the fundamentals justify stock payment, paying with cash is common. In that way, firms can preclude paying with undervalued stock and are more likely to experience positive long-term excess returns.